Volatilitas market cap pada Bursa Efek Indonesia periode 2019-2021 - Naili Amalia; Sunarso Sunarso (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Stocks are indeed one of the most sought after investments by investors. Stocks have the nature of active price movements, the speed at which stock prices rise or fall is often referred to as stock price volatility. As an investor, you need clear direction regarding the volatility of each layer of the market cap on the stock. Knowing the volatility in each layer of the market cap will provide considerations for investors before investing. This will involve consideration of the magnitude of the return and the risks to be faced. The higher the volatility of the stock price gives a signal, the higher the risk that will be faced. The lower the volatility, the signal the company tends to have a high market cap and has a lower risk. This research method uses quantitative methods with descriptive analysis research types and uses secondary data. The population of this study is the shares of companies listed on the IDX from 2019 to 2021 with purposive sampling where in each layer of the market cap, there are 30 companies. The results showed that there was a significant difference in the value of volatility in the market cap layer. While the results of the risk and return of each layer of the market cap have differences but are not significant.